Dynamics of Smart Parachute Airborne Deployment Using Broadcloth Canopy Instrumented with an Array of Weaved Distributed Fiber Optic Strain Sensors - Mendoza, Sebastian; Mendoza, Edgar; Prohaska, John; Antreas, Theodore; Esterkin, Yan; Theodosiou, Antreas; Kalli, Kyriacos; Kelsay, Connor; Lowry, Charles; Hill, Peter; Willey, Nicola; Crane, Richard (My University, 2022)
As space exploration programs around the world continue with accelerated plans for planetary robotic missions and human expeditions to Mars, the Moon, and beyond, laying the groundwork for even more complex human science expeditions, the need for spacecraft to land safely on planetary surfaces has become increasingly challenging because of the use of massive and hauling larger payloads required to accommodate the extended stays on the Martian and Lunar surface. Advances in supersonic decelerator technology investigates re-entry vehicle designs that evaluate reliable techniques for safe planetary atmospheric re-entry. Decelerator design engineers are investigating the use atmospheric drag as a solution to save rocket engines and fuel for final manoeuvres and landing procedures. The heavier planetary landers of tomorrow will require much larger drag devices use to slow them down during re-entry deployed at higher supersonic speeds to safely land vehicle, crew, and cargo. Aerial entry, descend, and landings system model validation and verification are an area in the aerodynamic decelerator community that is constantly growing and innovating.
Keywords: Smart Parachute Airborne; Fiber Optic Strain Sensors